DEVELOPMENT OF SIMULATION TECHNOLOGY FOR FORMING OF ADVANCED HIGH STRENGTH STEEL - Chen, Xiaoming (My University, 2012)
Advanced high strength steels (AHSS) exhibit significant higher springback and different fracture modes in forming processes and these problems cannot be accurately predicted using conventional simulation methods in many cases. In this thesis, new simulation technologies have been developed to improve the predictability for AHSS forming. The technologies integrated various aspects of simulation techniques, including development of material models and local formability criteria, calibration of the models with experimental data, and simulation method and parameter optimisations. Both laboratory and full scale parts were used to validate the simulation technologies developed. These technologies are originally applied to solve AHSS forming problems.
The springback predictions have been significantly improved using the newly developed simulation technology. The technologies include the implementation of the smooth contact to reduce contact errors, modification of mass scaling to reduce dynamic effect, implementation of isotropic/kinematic hardening model and optimization of simulation parameters. Shear fracture (a stretch bending fracture on a small radius) have been successful predicted using Modified Mohr Coulomb (MMC) fracture criterion. Both laboratory experiments and full scale parts have been used to validate the predictions. Shearing and pre-forming effects on hole expansion and edge stretching have been investigated. A new approach was introduced to evaluate AHSS sheared edge deformation and quality by measuring material flow line angle change on a shearing edge. Shearing processes were simulated using MMC failure criterion and the sheared edge deformation has been integrated to hole expansion simulation to produce a more accurate prediction. The pre-forming effect on edge cracking has been investigated through both experiments and simulations. The limit strains have been measured by experiments. Simulation technology was also developed to predict surface strains of pre-form and subsequent stretching. Formulation of plane stress characteristics considering normal anisotropy have been developed and applied to analyze the flange deformations and optimum blanks for cup drawing. The method of plane strain characteristics has been used to predict earing throughout the entire cup drawing process.
Keywords: Metal forming; FEA; AHSS; Springback; shear fracture; edge crack; Mechanical Engineering; Mechanical Engineering